2022
DOI: 10.3390/nu14235056
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition, Fruit Intake and Incident Stroke: A Prospective Chinese Cohort Study

Abstract: The aim of this study was to evaluate the association between fruit intake and stroke risk considering the genetic predisposition. We used data from 34,871 participants from the project of Prediction for Atherosclerotic Cardiovascular Disease Risk in China (China-PAR project) from 2007 to 2020. A polygenic risk score comprising 534 genetic variants associated with stroke and its related factors was constructed to categorize individuals into low, intermediate, and high genetic risk groups. The associations of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…In line with these results, our study found that a long‐term higher TFV intake was associated with a lower risk of incident hypertension. Recently, results from the same cohorts indicated that an increased TFV intake was associated with a decreased risk of stroke, cardiovascular disease (CVD), and all‐cause mortality 27,28 . These results are strongly supported by our findings that the incidence of hypertension, an important risk factor for incident CVD, decreased with increasing TFV intake.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In line with these results, our study found that a long‐term higher TFV intake was associated with a lower risk of incident hypertension. Recently, results from the same cohorts indicated that an increased TFV intake was associated with a decreased risk of stroke, cardiovascular disease (CVD), and all‐cause mortality 27,28 . These results are strongly supported by our findings that the incidence of hypertension, an important risk factor for incident CVD, decreased with increasing TFV intake.…”
Section: Discussionsupporting
confidence: 86%
“…(CVD), and all-cause mortality. 27,28 These results are strongly supported by our findings that the incidence of hypertension, an important risk factor for incident CVD, decreased with increasing TFV intake.…”
Section: Subgroup and Sensitivity Analysessupporting
confidence: 79%
“…Nonetheless, the most important finding is that four SNPs showed an association with APTT in the presence of a risk factor such as low consumption of fresh vegetables and fruits, suggesting that the prothrombotic effects of SERBP1 risk alleles are significantly modified by this risk factor. Low consumption of fresh vegetables and fruits primarily correlates with oxidative stress [44,45], the role of which in the risk of IS and IS-related phenotypes has been demonstrated in a substantial number of studies [6,[46][47][48][49][50]. Plant-based diets usually contain phenolic acids, flavonoids, and carotenoids, which have strong antioxidant properties and therefore eliminate an excess of active oxygen from the body and protect cells from damage, thereby reducing the risk of cardiovascular diseases [51].…”
Section: Low Fruit/vegetable Intake-related Correlates Of Serbp1mentioning
confidence: 99%
“…Wang et al [9] conducted a prospective cohort study that investigated the association between fruit intake and stroke with consideration for genetic disposition in a cohort of almost 35,000 individuals from the project Prediction for Atherosclerotic Cardiovascular Disease Risk in China (CHINA-PAR). This study reported that a greater amount of fruit consumption was associated with a lower risk of stroke (28-32%), whereby individuals who had a higher genetic risk of stroke may gain more benefits in terms of more stroke-free years and absolute risk reduction.…”
mentioning
confidence: 99%